Rhetorical Aspects of Popular Science - Maria Załęska (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2016)
After having distinguished the two main contexts for the transmission of knowledge – the esoteric and exoteric – the paper offers a systematic comparison between scientific and popular science texts in terms of inventio, dispositio and elocutio. The popular science texts tend to present knowledge in anthropocentric terms, showing the relevance of the message to the recipients’ everyday lives. They turn out to be shorter than genuine scientific texts, and this is achieved, in part, by eliminating information about the methodologies used. The user-friendly vocabulary offers the audience a sense of familiarity with the presented topic, which is, however, different from in-depth specialist knowledge.